Is multiculturalism bad for women? - Okin, Susan Moller (Book collections on Project MUSE., 1999)
This book brings together impressively varied voices who help to set the terms for discussing the relationship of feminism and multiculturalism. They show in no uncertain terms that feminists have something important to say to multiculturalists, and vice versa.